Keterlibatan Pelajar-Pelajar Luar Kampus Universiti Sains Islam Malaysia Dalam Memangkin Aktiviti Keagamaan Dan Sosial Bersama Masyarakat Setempat - Khairunneezam Mohd Noor; Mohd Asri Husain; Siti Suriani Othman; Amin Al Haadi Shafie; Mahazan Abdul Mutalib @ Talib (Universiti Sains Islam Malaysia, 2024)
A lot of intellectual discourses has been initiated on the realm of the contributions and roles of university students who live out of the campus, towards the community that they lived together. The Council of University Housing Principals of USIM had taken their initiative to look into the real views of the community who live nearby the university about the contributions and roles of university students who live out of the campus, specifically in the religious activities and social activities. A qualitative study through non-probability sampling method had been selected, where semistructured interviews were done among 30 individuals who live together with USIM outcampus students. The findings show that majority of the respondents agreed that the contributions and roles of the outcampus students were high and effective in the religious activities but not in the social activities. Several arising issues and themes of discussion are discussed together with recommendations to uphold a better relationship between USIM’s outcampus students and the community. Keywords: Outcampus students, Religious activities, Social activities